2011
DOI: 10.1038/pj.2011.42
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of polyethene–graft–polystyrene copolymers from linear polyethene-containing cyclopropane rings

Abstract: An efficient procedure to produce polyethene-graft-polystyrene (E-C3-graft-PS) copolymers by simple thermal treatment at 200 1C of polyethene (PE)-containing cyclopropane ring units (E-C3) in the presence of a high excess of styrene is reported. The high treatment temperature likely induces the breaking of the constrained cyclopropane rings, leading to the formation of radicals on the PE chains. The presence of styrene during the thermal treatment allows the formation of side polymer chains on the starting mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Isotactic poly( N ‐butenyl‐carbazole) ( i ‐PBK), isotactic and syndiotactic poly( N ‐pentenyl‐carbazole) ( i ‐PPK and s ‐PPK), and poly( N ‐hexenyl‐carbazole) ( i ‐PHK and s ‐PHK) were synthesized by using homogeneous Ziegler‐Natta (Z‐N) polymerization …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isotactic poly( N ‐butenyl‐carbazole) ( i ‐PBK), isotactic and syndiotactic poly( N ‐pentenyl‐carbazole) ( i ‐PPK and s ‐PPK), and poly( N ‐hexenyl‐carbazole) ( i ‐PHK and s ‐PHK) were synthesized by using homogeneous Ziegler‐Natta (Z‐N) polymerization …”
Section: Resultsmentioning
confidence: 99%
“…Isotactic poly(N-butenyl-carbazole) (i-PBK), isotactic and syndiotactic poly(N-pentenyl-carbazole) (i-PPK and s-PPK), and poly(N-hexenyl-carbazole) (i-PHK and s-PHK) were synthesized by using homogeneous Ziegler-Natta (Z-N) polymerization. [12][13][14][45][46][47][48][49][50] Rac-dimethylsilylbis(1-indenyl)zirconium dichloride (1)/MAO and diphenylmethylidene(cyclopentadienyl)-(9-fluorenyl)zirconium dichloride (2)/MAO (Scheme 2) were used as isospecific and syndiospecific catalytic systems, respectively.…”
Section: Polymer Synthesis and Microstructural Characterizationmentioning
confidence: 99%
“…As an example, it was shown that it is possible to produce crosslinked polyethylene by simple thermal treatments of such copolymers [35,36]. Moreover, by using a similar procedure, polyethylene-graft-polystyrene copolymers were prepared by thermal treatment at 200°C of polyethylene samples containing cyclopropane rings in the presence of a high excess of styrene [37]. Both processes were generated by radicals formed at high temperature from the breaking of the constrained cyclopropane rings.…”
Section: Introductionmentioning
confidence: 99%
“…The residue was purified by argentation flash chromatography (SiO cis,cis-3,4,13,14-Bismethylene-24-methyldotriacontane (4). Cyclopropanation was performed according to a modified procedure of Pragliola et al 52 A solution of AlEt 3 (1 M in hexane) was added to a stirred solution of diene 21 (25 mg, 0.054 mmol, 1.0 equiv) and CH 2 I 2 (13 μL, 0.163 mmol, 3.0 equiv) in CH 2 Cl 2 (1 mL). After stirring for 17 h at rt, NaF (42 mg, 0.540 mmol, 1.0 equiv) and H 2 O (1 mL) were added to the reaction mixture.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%